2013
DOI: 10.1039/c2ta00177b
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro-functionalization of vinylene units in a polyarylenevinylene for polymer solar cells

Abstract: A low band-gap copolymer PDTBTFV alternating bis-thienyl-(bis-alkoxy)-benzothiadiazole blocks with difluorovinylene units and its non-fluorinated counterpart PDTBTV have been synthesized and characterized as donor materials in bulk heterojunction (BHJ) solar cells with PCBM as the acceptor. The solar cells with the fluorinated polymer show better photovoltaic performances than those recorded with the non-fluorinated material. Comparative spectroscopic and computational studies, together with morphological, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 91 publications
0
22
0
Order By: Relevance
“…The synthetic routes of Monomer 1, Monomer 2, and PPBIBTE are illustrated in Scheme . The synthesis of compound 1,2,3,4 was prepared according to references .…”
Section: Methodsmentioning
confidence: 99%
“…The synthetic routes of Monomer 1, Monomer 2, and PPBIBTE are illustrated in Scheme . The synthesis of compound 1,2,3,4 was prepared according to references .…”
Section: Methodsmentioning
confidence: 99%
“…The same method was later extended to the synthesis of the two soluble conjugated polymers P22 and P23, in which the double bonds (either fluorinated or not) alternated with bis-thienyl-bis-alkoxybenzothiadiazole units (Scheme 10). [25] Scheme 10.…”
Section: Stille Couplingmentioning
confidence: 99%
“…Two copolymer of thienylvinylene with fluorination (P48) and without fluorination (P49) were synthesised by Cardone et al They found that the fluorination induces blue shift in the absorbance and lowering of the HOMO level. Additionally, the non-fluorinated polymer P49 showed a meagre PCE of less than 1% and the fluorinated counterpart P48 showed PCE of 1.24% [59]. Further, thienylenevinylene moiety was homopolymerised via Yamamoto technique and compared the homopolymers (P50) with copolymer of thienylenevinylene with benzothiadiazole (P51) and dithienylbenzothiadiazole (P52).…”
Section: Thienylvinylene Based Polymersmentioning
confidence: 99%